The effect of financial risks on the earnings response in Australian Bank Stocks. - Cheng, Fan-fah; Nasir, Annuar (EuroJournals Publishing, Inc., 2008)

(untitled)
Financial institutions are often treated differently from non-financial businesses. Therefore, this paper uses the concept from earnings response literature and extended with the banking risk management measures to find out whether the estimated financial risks have incremental content beyond earnings. This new procedure discovers that Australia investors priced the credit risk, which is measure by the provision for bad and doubtful debts, significantly in the earnings response valuation. This finding suggests the relevant of the credit exposure in the Australia banks using the latest data.